POLA PERSEPAN ANTIBIOTIK PADA PASIEN PNEUMONIA DI POLI ANAK RSUD DR. H. M. ANSARI SALEH BANJARMASIN TAHUN 2017 - Muhammad Zaini; Muliyani Muliyani; Jhudi Bonosari Soediono; Elisa Destiana (Jurnal Insan Farmasi Indonesia, 2019)
Pneumonia was a respiratory infection. Pneumonia was most often caused by bacterial, viral or mycoplasmic infections. The choice of therapy for pneumonia sufferers was generally given antibiotics. The purpose of this study was to determine the pattern of antibiotic use of pneumonia in pediatric patients in outpatient hospitals of dr. H. M. Ansari Saleh. The study was descriptive, data collection was carried out retrospectively in pneumonia patients who met the inclusion criteria was 52 samples. Data was taken from January to December 2017 through medical records. The results showed that pneumonia patients suffered the most from men by 26 cases (50%) and women by 26 cases (50%), based on the age of the most aged 1 - 12 months as many as 25 patients (48.07%). The use of antibiotics based on the selection of the most widely used groups is the third generation cephalosporins as many as 42 patients (80.76%), penicillin group as many as 6 patients (11.53%), the second generation cephalosporins as many as 4 patients (7.69%). The type of antibiotic that was often used is Cefixime as many as 46 users (88.46%), Amoxicillin as many as 6 users (11.53%), Cefadroxyl as many as 4 users (7.69%).